Fundamentals of criminal law : responsibility, culpability, and wrongdoing - Simester, A. P. (Oxford : Oxford University Press, 2021)
This volume explores the philosophical underpinnings of the law's major doctrines concerning actus reus, mens rea, and defences, showing that they are not always driven by culpability but are grounded also in principles of moral responsibility, ascriptive responsibility, and wrongdoing.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 11, 2021).
Keywords: Criminal law; Criminal liability